2000
DOI: 10.1016/s0304-3959(00)00284-0
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the concentrations of amino acids in the cerebrospinal fluid that correlate with pain in patients with fibromyalgia: implications for nitric oxide pathways

Abstract: Substance P (SP), a putative nociceptive transmitter, is increased in the CSF of patients with fibromyalgia syndrome (FMS). Because excitatory amino acids (EAAs) also appear to transmit pain, we hypothesized that CSF EAAs may be similarly involved in this syndrome. We found that the mean concentrations of most amino acids in the CSF did not differ amongst groups of subjects with primary FMS (PFMS), fibromyalgia associated with other conditions (SFMS), other painful conditions not exhibiting fibromyalgia (OTHER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(83 citation statements)
references
References 67 publications
1
78
0
4
Order By: Relevance
“…This concurs with the results from Perez-Neri et al [47] where no difference in the CSF arginine levels were observed between healthy human control and patients with infection and inflammatory processes in the CNS, even though both of these conditions are known to be associated with increased NO production. A study applying this very same method for NO analysis in CSF on patients with fibromyalgia has also shown an increase in citrulline level with increasing pain [48].…”
Section: Inhibitory Amino Acidsmentioning
confidence: 88%
“…This concurs with the results from Perez-Neri et al [47] where no difference in the CSF arginine levels were observed between healthy human control and patients with infection and inflammatory processes in the CNS, even though both of these conditions are known to be associated with increased NO production. A study applying this very same method for NO analysis in CSF on patients with fibromyalgia has also shown an increase in citrulline level with increasing pain [48].…”
Section: Inhibitory Amino Acidsmentioning
confidence: 88%
“…Of note, elevated levels of substance P, CGRP, and excitatory amino acids have been found in the cerebrospinal fluid of people with fibromyalgia 187,188 and CRPS.…”
Section: F Widespread Painmentioning
confidence: 99%
“…Later Omoigui [15] proposed the unifying theory of pain for which the source of all pain is inflammation and inflammatory response. The activation of pain receptors, transmission and modulation of pain signals, neuroplasticity and central sensitivity are all "one continuum" of inflammation and inflammatory response, he also suggested that the pain suffered by women with fibromyalgia it was as a result of neurogenic inflammation present in this disease [16].…”
Section: Inflammation and Fibromyalgiamentioning
confidence: 99%